H215O PET study of impairment of nonverbal recognition with normal aging. - Anderson, Karen E; Lynch, Katherine; Zarahn, Eric; Scarmeas, Nick; Van Heertum, Ronald; Sackeim, Harold; Moeller, James R; Stern, Yaakov (J Neuropsychiatry Clin Neurosci, 2005)
Little research has been conducted regarding age-related changes in nonverbal memory. Using positron emission tomography (PET), the authors studied 17 elderly volunteers and 20 young volunteers, during nonverbal recognition task performance, to examine differences in brain blood flow. The subjects were asked to recognize a study list size (SLS) of shapes that was adjusted so that each subject performed at approximately 75% accuracy. Positron emission tomography results showed that, relative to younger individuals, elderly subjects engaged different regions, including the insula, during recognition. Elderly subjects did not show the relationship between parahippocampal flow and SLS, which was observed in younger subjects. These differences suggest that age-related functional brain changes partly explain performance deficits.
Keywords: Adult; Aged; Aging; Brain; Cerebrovascular Circulation; Cognition Disorders; Female; Hippocampus; Humans; Image Processing, Computer-Assisted; Intelligence; Male; Memory; Neuropsychological Tests; Positron-Emission Tomography; Radiopharmaceuticals; Visual Perception